알루미늄-아연-마그네슘 합금의 원자단위 투과전자현미경 관찰 기반 η1 석출물 성장 고찰 - 김황선; Hwangsun Kim; 한흥남; Heung Nam Han (대한금속·재료학회지, 62(8), 2024)
Aluminum-Zinc-Magnesium (Al-Zn-Mg) alloys are extensively utilized in aerospace and automotive industries because of their exceptional mechanical properties and light weight. These properties of Al-Zn-Mg alloys are significantly influenced by the morphology, distribution, and size of the precipitates within the alloy, which result from the formation of numerous nanoscale precipitates. Among the various types of precipitates, η precipitates are the most representative, with the η1 variant comprising approximately 50% of the total η precipitates. In this study, we investigated the atomic-scale growth mechanism of η1 precipitates in Al-Zn- Mg alloys using high-resolution scanning transmission electron microscopy (STEM). The investigation revealed that the growth of η1 precipitates is driven by the separation of Mg and Zn atomic columns along the aluminum atomic arrangement near the interface, which facilitates the stepwise growth of the precipitates. Additionally, it was observed that a unique interfacial segregation layer forms in the direction of η1 precipitate growth, and energy-dispersive X-ray spectroscopy (EDS) confirmed that this layer is composed of Mg and Zn. These findings provide critical insights into the microscopic interactions and transformations that govern the precipitate formation process. This research offers valuable information for optimizing the microstructure and enhancing the mechanical performance of Al-Zn-Mg alloys for various high-performance applications.